Autophagosome formation and transcriptional activity of atg8 genes in Arabidopsis root cells during the development of autophagy under microgravity conditions - Shadrina, R.Yu.; Horiunova, I.I.; Blume, Ya.B.; Yemets, A.I. (Reports of the National Academy of Sciences of Ukraine, 2020)
Morphological and cytological analyses of Arabidopsis thaliana seedlings roots growing under conditions mimicking a microgravity has been performed. Moreover, we assessed the process of autophagy induction in cells upon such conditions. Here, we report significant changes in the root development and the enhanced autophagosome formation in epidermal cells in the transitional zone on the 6th day of cultivation upon conditions on a rotating clinostat, as well as their gradual decrease on the 9th and 12th days, respectively, in comparison to control plants. These changes may suggest the induction of the adaptive process to the microgravity conditions. Family of atg8 genes (atg8a, atg8b, atg8c, atg8d, atg8e, atg8f, atg8g, atg8h, and atg8i) are involved in the implementation of initial stages of autophagy. Transcriptional analysis of atg8 isoforms indicates clear time-dependent expression changes (6-12 days of microgravity) in the majority of such genes. In particular, the increased expression levels (atg8a, atg8c, atg8d) on the 6th day, a gradual decrease on the 9th day, and a significant decrease after 12 days of growing on a clinostat have been observed in comparison to control. Our results de monstrate the significantly elevated expression of atg8e, atg8f, and atg8i genes on the 6th, 9th, and 2th days. The obtained data suggest that studied atg8 genes are specifically involved in autophagy induced by microgravity in Arabidopsis thaliana.